One-step synthesis of a hierarchical self-supported WS2 film for efficient electrocatalytic hydrogen evolution. Issue 39 (23rd September 2019) - Wang, Min; Zhang, Li; Huang, Meirong; Zhang, Qifan; Zhao, Xuanliang; He, Yijia; Lin, Shuyuan; Pan, Jialiang; Zhu, Hongwei
Abstract : A tungsten disulfide film with a hierarchical structure is synthesized by surface-assisted chemical vapor transport method and applied as a self-supported electrode for the hydrogen evolution reaction, showing superior electrocatalytic performance. Abstract : The search for earth-abundant and inexpensive hydrogen evolution reaction (HER) electrocatalysts with excellent activity and durability to replace noble-metal-based electrocatalysts has a supreme effect on the scalable application of electrochemical water splitting. Transition metal dichalcogenides (TMDs) are attracting tremendous attention as potential substitutes for the HER, yet mostly suffer from insufficient exposed active sites and weak electrical contact with the support. Here we report a hierarchical tungsten disulfide (WS2 ) film in situ grown on tungsten foil by a one-step surface-assisted chemical vapor transport (SACVT) method. The hierarchical WS2 film is assembled from WS2 clusters that are made up of multi-oriented WS2 nanosheets, and can be applied as a self-supported electrode directly for the HER together with a metal substrate. The WS2 film displays superior electrocatalytic performance featuring a low overpotential (137 mV) to supply −10 mA cm −2 current density, a small Tafel slope (54 mV dec −1 ) and excellent catalytic durability in a long-term test (>200 h) in 0.5 M H2 SO4 . The outstanding electrocatalytic activity is mainly associated with the maximum exposure of active edge sites by the unique hierarchical structure of the WS2 film. Meanwhile, the in situ growth of WS2 on tungsten foil can ensure a close contact between them, which is favourable for enhancing the electrical conductivity and catalytic durability of the self-supported electrode. This result provides a straightforward and effective way for synthesizing efficient and robust self-supported WS2 film electrocatalysts for the HER in water splitting, and proposes a favorable direction for developing high-activity, low-cost and stable TMD electrocatalysts by constructing interesting hierarchical structures.